Does advancing male age influence the expression levels and localisation patterns of phospholipase C zeta (PLCζ) in human sperm? - Yeste, M; Jones, C; Amdani, S; Yelumalai, S; Mounce, G; Martins da Silva, S; Child, T; Coward, K (Nature Publishing Group, 2016)
Socio-economic factors have led to an increasing trend for couples to delay parenthood. However, advancing age exerts detrimental effects upon gametes which can have serious consequences upon embryo viability. While such effects are well documented for the oocyte, relatively little is known with regard to the sperm. One fundamental role of sperm is to activate the oocyte at fertilisation, a process initiated by phospholipase C zeta (PLCζ), a sperm-specific protein. While PLCζ deficiency can lead to oocyte activation deficiency and infertility, it is currently unknown whether the expression or function of PLCζ is compromised by advancing male age. Here, we evaluate sperm motility and the proportion of sperm expressing PLCζ in 71 males (22 – 54 years; 44 fertile controls and 27 infertile patients), along with total levels and localisation patterns of PLCζ within the sperm head. Three different statistical approaches were deployed with male age considered both as a categorical and a continuous factor. While progressive motility was negatively correlated with male age, all three statistical models concurred that no PLCζ–related parameter was associated with male age, suggesting that advancing male age is unlikely to cause problems in terms of the sperm’s fundamental ability to activate an oocyte.